Public Services, Public Acceptance, and Satisfaction: Macro Evaluation of Government Services in Sigi Regency - Muzakir Tawil; Yulizar Pramudika Tawil; giska mala rahmarini; Indra P P Salmon (Universitas Sultan Ageng Tirtayasa, 2021)
The background of this research is the justification of findings in the form of public services in Indonesia in general, which are not good and not satisfactory. The objectives of this research are; 1) testing the level of public satisfaction with the implementation of basic service programs in Sigi Regency (14 indicators), and; 2) testing the level of public acceptance of the implementation of development programs in Sigi Regency (9 indicators). We use a mix-method approach in analyzing the results of public satisfaction and public acceptance to obtain the depth of data and field results. The results showed that the index of public acceptance of public services in Sigi Regency was 3.92, which means that the majority of Sigi Regency people received local government programs simultaneously. Partially, there are three dimensions in the form of program effectiveness, program efficiency, and dimensions of trust concerning the index of public acceptance of public services in Sigi Regency which is below the average score. However, this dimension does not simultaneously affect the level of public trust in public services in Sigi Regency with a total increase of 76.02%. The implication of this research is the existence of alternative strategies for improvement to improve public acceptance (IPM) and public satisfaction (IKM), including efficiency and public trust in the public acceptance index (IPM) framework, as well as safety and comfort within the public satisfaction index framework (IKM).Keywords: public service; public acceptance index; public satisfaction index; Sigi Regency.